Impact of self-directed learning readiness and learning attitude on problem-solving ability among Chinese undergraduate nursing students - Luo Ru-Zhen; Zhang Xiao-Hong; Zhang Chun-Mei; Liu Yan-Hui (Sciendo, 2019)
To explore the effects of self-directed learning readiness and learning attitude on problem-solving ability among Chinese undergraduate nursing students.